Design of a Full-Ocean-Depth Macroorganism Pressure-Retaining Sampler and Fluid Simulation of the Sampling Process - Guangping Liu; Yongping Jin; Youduo Peng; Deshun Liu; Buyan Wan (Journal of Marine Science and Engineering, 2022)
Hadal seafloor organisms live under ultra-high pressure, in low temperatures, and other environments for a long time, which puts higher requirements on the structural design of deep-sea biological samplers. In this paper, we present a full-ocean-depth hydraulic suction macroorganism pressure-retaining sampling method, which actively samples seafloor macroorganisms by pumping and stabilizing the pressure inside the sampler using a pressure compensator. Firstly, the structure and working principle of the hydraulic suction macroorganism pressure-retaining sampler (HSMPS) were introduced. Then the flow field of the HSMPS sampling process was analyzed, and the velocity and pressure distribution of the flow field at different locations of the HSMPS were obtained. In response to the problem of the low viability of samples collected by deep-sea biological samplers, the changes in radial velocity and pressure at different positions of the sampler under different pumping flows were analyzed. Finally, the appropriate suction flow rate was selected based on the analysis results, and HSMPS suction tests and simulated sampling tests, under a 110 MPa high-pressure environment, were carried out using the developed HSMPS engineering prototype. The test results verify the feasibility of the HSMPS design, which will provide strong support for the deep abyssal seafloor sampling operation of the full-ocean-depth manned submersible.